СУБ’ЄКТИВНА СТОРОНА ЗЛОЧИНУ, ПЕРЕДБАЧЕНОГО Ч. 1 СТ. 139 КРИМІНАЛЬНОГО КОДЕКСУ УКРАЇНИ - Берило, Олександр Георгійович (SUPREMANCE OF LAW, 2017)
The article examines characteristics of subjective aspect of the failure to assist a sick person by a medical worker. The author draws attention to the fact that the criminal law does not explicitly indicate the form of guilty of a medical worker who fails to assist a sick person in the qualified form of the crime, insofar as there are different points of view on this issue in the criminal legal literature. However, the presence in part 1 of Art. 139 of the Criminal Code of Ukraine of the phrase “if it is known...” indicates a direct intent. This crime is committed for certain motives which although not specifi ed in the law as a compulsory feature, have in each case an important criminal law signifi cance.